2002
DOI: 10.1101/gr.223902
|View full text |Cite
|
Sign up to set email alerts
|

The Genome of M. acetivorans Reveals Extensive Metabolic and Physiological Diversity

Abstract: Methanogenesis, the biological production of methane, plays a pivotal role in the global carbon cycle and contributes significantly to global warming. The majority of methane in nature is derived from acetate. Here we report the complete genome sequence of an acetate-utilizing methanogen, Methanosarcina acetivorans C2A. Methanosarcineae are the most metabolically diverse methanogens, thrive in a broad range of environments, and are unique among the Archaea in forming complex multicellular structures. This dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
456
0
3

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 580 publications
(467 citation statements)
references
References 56 publications
8
456
0
3
Order By: Relevance
“…However, no additional nif gene cluster encoding a potential alternative nitrogenase was observed in the complete M. mazei genome sequence. This is in contrast to the genome sequences of M. acetivorans and M. barkeri, which contain three and at least two sets of nif genes, respectively (Chien et al 2000, Galagan et al 2002; ERGO database (Integrated Genomics, Inc., http://www. integratedgenomics.com) and ORNL database (http://genome.ornl.gov/microbial/mbar)).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, no additional nif gene cluster encoding a potential alternative nitrogenase was observed in the complete M. mazei genome sequence. This is in contrast to the genome sequences of M. acetivorans and M. barkeri, which contain three and at least two sets of nif genes, respectively (Chien et al 2000, Galagan et al 2002; ERGO database (Integrated Genomics, Inc., http://www. integratedgenomics.com) and ORNL database (http://genome.ornl.gov/microbial/mbar)).…”
Section: Resultsmentioning
confidence: 97%
“…The discovery of genes homologous to nifH, nifD and nifK suggests that the basic mechanism of nitrogen fixation is similar in Bacteria and Archaea and predicts that most methanogenic nitrogenases contain a molybdenum-cofactor Zinder 1996, Kessler et al 1997). It was recently shown that, unique among the archaea, Methanosarcina acetivorans appears to contain all three types of nitrogenases: the molybdenum nitrogenase and two alternative nitrogenases (Galagan et al 2002). In methanogenic archaea, the nitrogen fixation genes nifH, nifD, nifK, nifE and nifN are present in the same order as in bacteria (Dean and Jackobson 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The Halobacterium genome also contains multiple copies of TFB-encoding genes (seven), as do half of the other genomes that contain either two or three copies. Hence, the identification of multiple copies of TBP and TFB genes in a range of archaeal species supports the hypothesis that different types of transcriptional regulation occur in response to environmental challenges (Goo et al 2004), although the role of multiple TBPs and their relationship with multiple TFBs is not yet clear (Galagan et al 2002).…”
Section: Discussionmentioning
confidence: 71%
“…In contrast to the widespread occurrence of selenocysteine, the distribution of pyrrolysine is so far known only in a handful of methanogenic archaea and bacteria (Galagan et al+, 2002;Srinivasan et al+, 2002)+ The central metabolism of these organisms is the catabolic conversion of methylamines, which requires a family of mono-, di-, and trimethylamine methyltransferases+ Many of the methyltransferase genes of the methanogen Methanosarcina barkeri are interrupted by in-frame amber codons; tryptic peptide sequencing of one such protein (MtmB) showed that the amber codon is decoded as lysine (James et al+, 2001)+ The determination of the X-ray structure of MtmB to a resolution of 1+55 Å showed additional electron density best described as a lysine in an amide linkage to a 4-substitutedpyrroline-5-carboxylate (Hao et al+, 2002)+ This unusual amino acid suggests a plausible (though as yet unproven) mechanism for the methyltransferase reaction (Hao et al+, 2002)+ The machinery necessary for pyrrolysine insertion in M. barkeri appears to reside in a unique gene cluster that includes an amber suppressing tRNA (pylT ), an unusual lysyl-tRNA synthetase (pylS ), and additional proteins provisionally responsible for converting lysine to pyrrolysine (Srinivasan et al+, 2002)+ The tRNA encoded by pylT differs significantly from canonical tRNAs+ The anticodon arm has 6 rather than 5 bp, the variable loop has 3 rather than 4 nt, and the nearly universally conserved D-loop GG and T-loop TcC sequences are absent+ These features are likely to be important for recognition by the dedicated pylS gene product, which resembles the class II tRNA synthetases in its C-terminal catalytic domain+ However, the N-terminal domain of the pylS lysyl-tRNA synthetase possesses negligible sequence identity with the anticodon binding domains of other class IIb synthetases, which are based on the OB fold+ An in-frame amber codon is also found in the mttB gene of the gram-positive bacterium Desulfitobacterium hafniense, and it is likely decoded as pyrrolysine by a cotranslational mechanism similar to that of selenocysteine+ In D. hafniense, however, pylS is split into two ORFs that separately encode the N-and C-terminal domains+ The presence of an unusual LysRS for pyrrolysine suggests that tRNA Lys(Pyl) has diverged beyond the point of recognition by LysRS-I or LysRS-II+ Features of the translation machinery that allow context dependent insertion of pyrrolysine remain to be identified, and constitute an interesting follow-up question+…”
Section: Natural Expansions Of the Genetic Code: Selenocysteine And Pmentioning
confidence: 99%